Renewable energy support policy based on contracts for difference and bilateral negotiation - Algarvio, Hugo (2020)
ABSTRACT: The European Union has been one of the major drivers of the development of renewable energy. The energy policies of most European countries have involved subsidized tariffs, such as the feed-in tariff in Portugal, the regulated tariff and the market price plus premium in Spain, and the Renewables Obligation in UK, that came into effect in 2002. Recently, UK has made some reforms and started to consider contracts for difference (CfDs) as a key element of the energy policy. This paper presents a support policy based on CfDs and bilateral negotiation. The first phase consists in a CfD auction and the second phase involves a bilateral negotiation between a Government and each of the selected investors. The paper also presents a case-study to analyze the potential benefits of the support policy. It was performed with the help of the MATREM system. The preliminary results indicate some advantages for the Government (and, in some cases, for the investors as well).